Lymphocutaneous Sporotrichosis during Treatment with Anti-TNF-Alpha Monotherapy - Francesco Ursini; Emilio Russo; Christian Leporini; Marilena Calabria; Caterina Bruno; Cesare Tripolino; Saverio Naty; Rosa Daniela Grembiale (Case Reports in Rheumatology)
Sporotrichosis is an infectious disease caused by Sporothrix schenckii, a dimorphic fungus isolated for the first time in 1896 by Benjamin Schenck from a 36-year-old male patient presenting lesions on the right hand and arm. The infection generally occurs by traumatic inoculation of soil, plants, and organic matter contaminated with the fungus. Different clinical syndromes are described as a direct consequence of S. schenckii infection, including lymphocutaneous and disseminated forms, although extracutaneous presentations are reported most frequently in AIDS patients. Here we describe the case of a 57-year-old Caucasian male diagnosed in 2004 with ankylosing spondylitis under stable treatment with adalimumab monotherapy (40 mg every other week). During a routine follow-up visit in March 2013, he presented with multiple nodular lesions arranged in a linear fashion along the left hand and forearm. After diagnostic aspiration of the lesions, lymphocutaneous sporotrichosis was diagnosed and appropriate therapy started.